Antiterapias, by Jacques Fux: reading put into metafiction - Silva, Vera Lopes da (2020)
This study is dedicates itself to reflecting about the narrator category in Antiterapias, by Jacques Fux, in order to elucidate the metanarrative way to operate the work, his constructive action of a reader-writer-narrator, a projection motivated in and by contemporality. The work illustrates the relation between reading and creating, faces that tangle together and draw a map of readings. It is about a composition conceived as a testimony manifested in the acting of a reader that projects himself as a writer that narrates himself in his dispersions in a labyrinthic library.